(untitled) (Research, Society and Development, 2020)
Objective: Evaluate the pre-gestational and maternal nutritional profile from prenatal care. Method: This is a cross-sectional study, developed in a reference maternity hospital in high-risk pregnancies in the state of Amazonas, in the period from May to November 2019, with a non-probabilistic sample of 108 puerperal women. Data collection was done with a pre-prepared instrument and consultation of information on prenatal cards.Results:​ It were evaluated 108 puérperas, being more frequent women from 20 to 34 years old (70,4%), complete high school (37,0%), consensual union (50,9%), brown color (85,2%), familiar income until three minimum wages (98,1%), non-smokers (94,4%) and non alcoholists (84,3%). Referring to the registers on the prenatal card, it was observed the absence of the nutritional evaluation (Atalah curve), on the three pregnancy quarters (90,4%, 91,8% and 89,1%), respectively. The evaluation performed by the research team, identified greater frequency for the eutrophic profile both in the pre-gestational period (51.9%), as in the first (43.2%), second (39.6%) and third quarters of pregnancy (36.7%). However, variations for low weight, overweight and obesity were also observed, showing changes in the behavior of the nutritional profile during the gestational period, and not identified in prenatal care. Conclusion: Although most of them present an eutrophic profile, in the prenatal and gestational periods, the absence of registers and evaluations in the prenatal cards, consist in an obstacle for the early detection of alterations in the nutritional profile, resulting in unfavorable outcomes related to maternal morbidities.